National experience with adenosine deaminase deficiency related SCID in Polish children - Dąbrowska-Leonik, Nel; Piątosa, Barbara; Słomińska, Ewa; Bohynikova, Nadezda; Bernat-Sitarz, Katarzyna; Bernatowska, Ewa; Wolska-Kuśnierz, Beata; Kałwak, Krzysztof; Kołtan, Sylwia; Dąbrowska, Anna; Goździk, Jolanta; Ussowicz, Marek; et al. (Frontiers in Immunology, 2023)
Introduction Deficiency of adenosine deaminase (ADA) manifests as severe combined immunodeficiency (SCID), caused by accumulation of toxic purine degradation by-products. Untreated patients develop immune and non-immune symptoms with fatal clinical course. According to ESID and EBMT recommendations enzyme replacement therapy (ERT) should be implemented as soon as possible to stabilize the patient’s general condition, normalize transaminases, treat pulmonary proteinosis, bone dysplasia, and protect from neurological damage. Hematopoietic stem cell transplantation (HSCT) from a matched related donor (MRD) is a treatment of choice. In absence of such donor, gene therapy (GT) should be considered. HSCT from a matched unrelated donor (MUD) and haploidentical hematopoietic stem cell transplantation (hHSCT) are associated with worse prognosis. Material and methods We retrospectively evaluated the clinical course and results of biochemical, immunological and genetic tests of 7 patients diagnosed in Poland with ADA deficiency since 2010 to 2022. Results All patients demonstrated lymphopenia affecting of T, B and NK cells. Diagnosis was made on the basis of ADA activity in red blood cells and/or genetic testing. Patients manifested with various non-immunological symptoms including: lung proteinosis, skeletal dysplasia, liver dysfunction, atypical hemolytic-uremic syndrome, and psychomotor development disorders. Five patients underwent successful HSCT: 3 patients from matched unrelated donor, 2 from matched sibling donor, and 1 haploidentical from a parental donor. In 4 patients HSCT was preceded by enzyme therapy (lasting from 2 to 5 months). One patient with multiple organ failure died shortly after admission, before the diagnosis was confirmed. None of the patients had undergone gene therapy. Conclusions It is important to diagnose ADA SCID as early as possible, before irreversible multi-organ failure occurs. In Poland HSCT are performed according to international immunological societies recommendations, while ERT and GT are less accessible. Implementation of Newborn Screening (NBS) for SCID in Poland could enable recognition of SCID, including ADA-SCID.